2017
DOI: 10.1186/s12915-017-0445-8
|View full text |Cite
|
Sign up to set email alerts
|

Erv1 of Arabidopsis thaliana can directly oxidize mitochondrial intermembrane space proteins in the absence of redox-active Mia40

Abstract: BackgroundMany proteins of the mitochondrial intermembrane space (IMS) contain structural disulfide bonds formed by the mitochondrial disulfide relay. In fungi and animals, the sulfhydryl oxidase Erv1 ‘generates’ disulfide bonds that are passed on to the oxidoreductase Mia40, which oxidizes substrate proteins. A different structural organization of plant Erv1 proteins compared to that of animal and fungal orthologs was proposed to explain its inability to complement the corresponding yeast mutant.ResultsHerein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…However, the diversification in the position of the distal/shuttle disulfide may reflect an adaptation of the basic catalytic machinery to specific requirements found in some species. For instance, the human ALR fully complements the yeast erv1 mutant (Sztolsztener et al ., ), whereas the A. thaliana ERV1 counterpart is quite ineffective (Peleh et al ., ).…”
Section: The Disulfide Relay In the Mitochondrial Intermembrane Spacementioning
confidence: 97%
See 2 more Smart Citations
“…However, the diversification in the position of the distal/shuttle disulfide may reflect an adaptation of the basic catalytic machinery to specific requirements found in some species. For instance, the human ALR fully complements the yeast erv1 mutant (Sztolsztener et al ., ), whereas the A. thaliana ERV1 counterpart is quite ineffective (Peleh et al ., ).…”
Section: The Disulfide Relay In the Mitochondrial Intermembrane Spacementioning
confidence: 97%
“…An important difference for this molecular interaction is that the distal disulfide in plant ERV1 is situated in the C‐terminal part. Although there is currently no structural information regarding how plant MIA40 and ERV1 interact together, we recently observed that A. thaliana ERV1 does poorly oxidize the yeast MIA40 both in vitro and in vivo (Peleh et al ., ). In fact, the C‐terminal arm containing the cysteine pair forming the distal disulfide in A. thaliana ERV1 does not form the amphipathic helix that is usually found in MIA40‐interacting proteins.…”
Section: The Disulfide Relay In the Mitochondrial Intermembrane Spacementioning
confidence: 97%
See 1 more Smart Citation
“…Also in plants, Erv1 can directly bind substrates making Mia40 dispensable. Unfortunately, little is known about the mechanisms of protein translocation in these organisms and other, so far not characterized factors might take over the holdase and foldase function of Mia40 (Carrie et al, 2010 ; Eckers et al, 2013 ; Haindrich et al, 2017 ; Peleh et al, 2017 ).…”
Section: Final Remarksmentioning
confidence: 99%
“…The power of this process stems from the oxidizing effect of oxygen. Interestingly, recent work by Peleh et al published in BMC Biology provides evidence that certain sulfhydryl oxidases from the IMS can promote the oxidative folding of substrates independently of any oxidoreductase [ 2 ]. This supports the idea that in the IMS of mitochondria the pathway evolved in a stepwise manner from a pathway utilizing only a sulfhydryl oxidase to one containing both a sulfhydryl oxidase and an oxidoreductase [ 3 ].…”
Section: Commentarymentioning
confidence: 99%